Regional Financial Model Mapping Independence to Fiscal in East Java - Syamsul Huda (Future Science)
With the advent of Law No .22 years 1999 set an authority and responsibility from central government to local government and UUNo.25 1999 governing financial between the center and regions, especially in the District city in East Java n local resources and reduce the dependence of the center.This study aims to determine the independence of the Regency/City in East Java analysis used is qualitative analysis, the analysis that is explained in the description or in the form of sentences. This study aims to determine the independence of the Regency / City in East Java analysis used is qualitative analysis, the analysis that is explained in the description or in the form of sentences and quantitative analysis, namely analysis using formulas and definite analysis. Quantitative analysis includes the analysis of the degree of fiscal decentralization determine the level of independence of regional and by sector economic potential in the District East Java so that it can determine the level of financial independence and economic potential of the region. Result are expected to be used a pattern of the relationship between the central government and the government in the district /city in East Java as well as the formula right policy for future economic development.From this research, it is known that the city of Surabaya has a degree of fiscal autonomy for PAD at 48% of revenue while the region Gresik on the degree of fiscal autonomy degree “Enough” and Sidoarjo district in degrees. There are 32 regions in the East Java degree of fiscal independence of each very less independent, meaning of Balance Funds as well as from centers of the province.